2017
DOI: 10.18632/oncotarget.23786
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress promotes exit from the stem cell state and spontaneous neuronal differentiation

Abstract: Reactive oxygen species (ROS) play important roles in fundamental cellular processes such as proliferation and survival. Here we investigated the effect of oxidative stress on stem cell maintenance and neuronal differentiation in a human embryonic stem cell (hESC) model, Ntera2 (NT2). CM-H2DCFDA and DHE assays confirmed that the oxidizing agent paraquat could induce a high level of ROS in NT2 cells. Quantitative PCR, Western blotting and immunocytochemistry showed that paraquat-induced oxidative stress suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 52 publications
3
45
0
Order By: Relevance
“…To investigate whether extranuclear NANOG colocalizes with centrosomes, we performed double indirect immunofluorescence using an anti-pericentrin antibody specific for the detection of centrosomes ( Figure 2) combined with each of the two independent anti-NANOG commercial antibodies (Figure 3a-c). In addition to rhabdomyosarcoma cell lines, we also examined established and patient-derived tumor cell lines of neurogenic origin, as well as the NTERA-2 human pluripotent embryonal carcinoma cell line, which served as a positive control of nuclear NANOG expression [39]. Indeed, the localization of the fluorescence signal for NANOG colocalized with centrosomes in each of the nine examined tumor cell lines (Figure 3a-c).…”
Section: Centrosomal Localization Of the Nanog Proteinmentioning
confidence: 99%
“…To investigate whether extranuclear NANOG colocalizes with centrosomes, we performed double indirect immunofluorescence using an anti-pericentrin antibody specific for the detection of centrosomes ( Figure 2) combined with each of the two independent anti-NANOG commercial antibodies (Figure 3a-c). In addition to rhabdomyosarcoma cell lines, we also examined established and patient-derived tumor cell lines of neurogenic origin, as well as the NTERA-2 human pluripotent embryonal carcinoma cell line, which served as a positive control of nuclear NANOG expression [39]. Indeed, the localization of the fluorescence signal for NANOG colocalized with centrosomes in each of the nine examined tumor cell lines (Figure 3a-c).…”
Section: Centrosomal Localization Of the Nanog Proteinmentioning
confidence: 99%
“…Higher concentrations of ROS (100 μM H 2 O 2 ) have been shown to increase the production of neuronal and oligodendroglial cells from neural precursor cells under differentiation conditions . Indeed, oxidative stress has been suggested to promote neuronal differentiation of NSPCs . Given the similarities between SVZ cells in the brain and spinal cord ependymal NSPCs, it is likely that many of the responses to ROS described within the brain also hold true for NSPCs in the spinal cord.…”
Section: Ros Regulates Nspc Proliferation Differentiation and Survivalmentioning
confidence: 99%
“…41 Indeed, oxidative stress has been suggested to promote neuronal differentiation of NSPCs. 42 Given the similarities between SVZ cells in the brain and spinal cord ependymal NSPCs, it is likely that many of the responses to ROS described within the brain also hold true for NSPCs in the spinal cord. However, only a small number of studies have specifically examined the effects of ROS on ependymal NSPCs to definitively confirm this postulate, and these studies showed that much higher levels of ROS (500 μM) are required to induce cell death in vitro compared with differentiated neurons.…”
Section: Nspcs Display a Unique Response To Ros Studies Conducted Onmentioning
confidence: 99%
“…Moreover, mitochondrial ROS levels are crucial for the biological functions of stem cells (Zuluaga, Barzegari, Letourneur, Gueguen, & Pavon‐Djavid, 2017). Low levels of mitochondrial ROS production are demanded in some cellular processes such as proliferation and differentiation (Q. Hu, Khanna, et al, 2018; Pashkovskaia, Gey, & Rödel, 2018). It has been reported that the primary human mesenchymal stem cells (MSCs) may differentiate into adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of mitochondrial ROS production are demanded in some cellular processes such as proliferation and differentiation (Q. Hu, Khanna, et al, 2018;Pashkovskaia, Gey, & Rödel, 2018). It has been reported that the primary human mesenchymal stem cells (MSCs) may differentiate into adipocytes.…”
mentioning
confidence: 99%